NMDA receptor binding in focal epilepsies. Issue 10 (19th May 2015) - McGinnity, C J; Koepp, M J; Hammers, A; Riaño Barros, D A; Pressler, R M; Luthra, S; Jones, P A; Trigg, W; Micallef, C; Symms, M R; Brooks, D J; Duncan, J S
Abstract : Objective: To demonstrate altered N -methyl-d -aspartate (NMDA) receptor availability in patients with focal epilepsies using positron emission tomography (PET) and [ 18 F]GE-179, a ligand that selectively binds to the open NMDA receptor ion channel, which is thought to be overactive in epilepsy. Methods: Eleven patients (median age 33 years, 6 males) with known frequent interictal epileptiform discharges had an [ 18 F]GE-179 PET scan, in a cross-sectional study. MRI showed a focal lesion but discordant EEG changes in two, was non-localising with multifocal EEG abnormalities in two, and was normal in the remaining seven patients who all had multifocal EEG changes. Individual patient [ 18 F]GE-179 volume-of-distribution (VT ) images were compared between individual patients and a group of 10 healthy controls (47 years, 7 males) using Statistical Parametric Mapping. Results: Individual analyses revealed a single cluster of focal VT increase in four patients; one with a single and one with multifocal MRI lesions, and two with normal MRIs. Post hoc analysis revealed that, relative to controls, patients not taking antidepressants had globally increased [ 18 F]GE-179 VT (+28%; p<0.002), and the three patients taking an antidepressant drug had globally reduced [ 18 F]GE-179 VT (−29%; p<0.002). There were no focal abnormalities common to the epilepsy group. Conclusions: In patients with focal epilepsies, we detected primarily global increases of [ 18 F]GE-179 VT consistent with increased NMDA channel activation, but reduced availability in those taking antidepressant drugs, consistent with a possible mode of action of this class of drugs. [ 18 F]GE-179 PET showed focal accentuations of NMDA binding in 4 out of 11 patients, with difficult to localise and treat focal epilepsy.